Julius Caesar - "Shakespeare, William" (sweet cherry: China, 2013)
Julius Caesar is one of the greatest tragedies of William Shakespeare. The play is set in ancient Rome and portrays actual events from Roman history. As the play unfolds, the evil conspiracy of Caesar s murder is revealed. Great tragedy strikes Rome when Caesar is murdered, and this is followed by the downfall of his conspirators. This short narrative version of the play has been suitably adapted to help introduce the play to young readers. It can be read by children or read to them by parents who wish to introduce them to the play
Keywords: Adaptations Juvenile literature